A mechanical–thermal noise analysis of a nonlinear microgyroscope. (15th January 2017) - Lajimi, S.A.M.; Heppler, G.R.; Abdel-Rahman, E.M.
Abstract: The mechanical–thermal noise (MTN) equivalent rotation rate ( Ω n ) is computed by using the linear approximation of the system response and the nonlinear "slow" system. The slow system, which is obtained using the method of multiple scales, is used to identify the linear single-valued response of the system. The linear estimate of the noise equivalent rate fails as the drive direction stroke increases. It becomes imperative in these conditions to use a more complex nonlinear estimate of the noise equivalent rate developed here for the first time in literature. The proposed design achieves a high performance regarding noise equivalent rotation rate.